Agricultural production in Communist China, 1949-1965: chapters 1 and 2 - Chao, Gang (Madison: University of Wisconsin Press, 1970)
This book provides an insight to the china renewal program on economic and development. it further explain the Chinese unique system in governance.
asm; 25/01/19
Loans
Keywords: Agriculture; Agricultural production; China